Etyczna norma „nie czyń poważnych szkód” w perspektywie zasady odpowiedzialności za przyszłość. Regulacyjne implikacje dla etyki biznesu - Sroka, Robert (Humaniora. Czasopismo Internetowe, 2025)
In recent years, a series of regulations for business have been introduced in the European Union, aimed at achieving the agreements on limiting climate change signed during the Paris agreements, as well as attempting to redefine the role of business in socjety by changing business models – from those in which entrepreneurs privatized profits and externalized costs, to one where the negative social impact will not only be minimized but, first and foremost, taken into account in the business operations of those companies. This change is based on the ethical principle of “do no significant harm.” The purpose of this article is to attempt to expand the justification for applying the “do no significant harm” principle with philosophical arguments. The first part presents the “do no significant harm” principle contained in the discussed regulations, while the second part attempts to deepen this principle based on philosophical considerations of responsibility for the future, as discussed by Hans Jonas and Dieter Birnbacher. In this article, I propose replacing the temporal perspective of the “do no significant harm” principle with a horizontal perspective.